Lay Beliefs About Interaction Quality: An Expertise Perspective on Individual Differences in Interpersonal Emotion Ability - Wild, Marcus G.; Bachorowski, Jo-Anne (Frontiers in Psychology, 2020)
Social interactions are a source of lay beliefs about the ways in which psychological constructs operate. Some of the most enduring psychological constructs to become common lay beliefs originated from research focused on social-emotional processes. “Emotional intelligence” and “social intelligence” are now mainstream notions, stemming from their appealing nature and depiction in popular media. However, empirical attempts at quantifying the quality of social interactions have not been as successful as measures of individual differences such as social skills, theory of mind, or social/emotional intelligence. The subjective, lay ratings of the quality of interactions by naïve observers are nonetheless consistent both within and between observers. The goal of this paper is to describe recent empirical work surrounding lay beliefs about social interaction quality and ways in which those beliefs can be quantified. We will then argue that these lay impressions formed about the quality of an interaction, perhaps via affect induction, are consistent with an expertise framework. Affect induction creates instances in memory that accumulate over the lifespan and are ultimately measurable as social-emotional expertise (SEE). The ways in which our lay beliefs about social interaction quality fit the definition of expertise, the automatic, holistic processing of relevant stimuli, will be discussed. We will then describe the promise of future work in this area, with a focus on a) continued delineation of the thoughts, behaviors, and timing of behaviors that lead to high-quality social interactions; and b) the viability of expertise as the conceptual model for individual differences in social-emotional ability.